2002
DOI: 10.4049/jimmunol.168.3.1372
|View full text |Cite
|
Sign up to set email alerts
|

15-Deoxy-Δ12,1412,14-PGJ2 Induces IL-8 Production in Human T Cells by a Mitogen-Activated Protein Kinase Pathway

Abstract: Mast cells, platelets, and some macrophages are abundant sources of PGD2 and its active metabolite 15-deoxy-Δ12,14-PGJ2 (15-d-PGJ2). The lipid mediator 15-d-PGJ2 regulates numerous processes, including adipogenesis, apoptosis, and inflammation. The 15-d-PGJ2 has been shown to both inhibit as well as induce the production of inflammatory mediators such as TNF-α, IL-1β, and cyclooxygenase, mostly occurring via a nuclear receptor called peroxisome proliferator-activated receptor-γ (PPAR-γ). Data concerning the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
63
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(69 citation statements)
references
References 54 publications
(45 reference statements)
5
63
1
Order By: Relevance
“…Because PPAR-␥ gene and protein expressions are up-regulated and its protein localization to the nucleus is promoted by AM/AMBP-1, we propose that this is a major pathway of the anti-inflammatory effect of AM/AMBP-1. We have previously shown that PPAR-␥ activation is in fact responsible for the down-regulation of LPS-induced TNF-␣ release in inhibition studies using GW9662, a PPAR-␥ selective antagonist (51). In this model, the AM/AMBP-1-mediated up-regulation of PPAR-␥ seems to play a greater role than the LPS-mediated suppression of PPAR-␥ in the regulation of TNF-␣ response.…”
Section: Discussionmentioning
confidence: 84%
“…Because PPAR-␥ gene and protein expressions are up-regulated and its protein localization to the nucleus is promoted by AM/AMBP-1, we propose that this is a major pathway of the anti-inflammatory effect of AM/AMBP-1. We have previously shown that PPAR-␥ activation is in fact responsible for the down-regulation of LPS-induced TNF-␣ release in inhibition studies using GW9662, a PPAR-␥ selective antagonist (51). In this model, the AM/AMBP-1-mediated up-regulation of PPAR-␥ seems to play a greater role than the LPS-mediated suppression of PPAR-␥ in the regulation of TNF-␣ response.…”
Section: Discussionmentioning
confidence: 84%
“…Similarly, Ward et al (2002) recently showed that 15-PGJ 2 exploits PPARg-independent inhibition of NF-kB activation to induce caspase-dependent apoptosis in granulocytes. Other mediators that have been implicated in PPARg-independent properties of 15-PGJ 2 and can potentially have a similar function in cancer cells include AP-1 (Boyault et al, 2001), MAP kinase (Harris et al, 2002;Lennon et al, 2002), and reactive oxygen species (Li et al, 2001;Lennon et al, 2002). The latter has been shown to act as intermediates for the induction of apoptosis caused by 15-PGJ 2 in human myofibroblasts (Li et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a PPAR␥-mediated inhibition of NF-B together with NF-AT and AP-1 DNA binding activity and repression of the transactivation driven by these transcription factors has been described in human T cells that correlated with inhibition of proliferation, IL-2 production, and promoter activation in the presence of synthetic and natural PPAR␥ activators including 15d-PGJ 2 (67, 68 2 has been shown to induce IL-8 production via activation of mitogen-activated protein kinases together with the NF-B and AP-1 transcription factors (69). In this case the effect was not related to PPAR␥, as synthetic PPAR␥ agonists did not mimic the 15d-PGJ 2 -mediated IL-8 induction.…”
Section: Discussionmentioning
confidence: 99%